2022
DOI: 10.21303/2313-8416.2022.002551
|View full text |Cite
|
Sign up to set email alerts
|

Reserves of resource saving in the manufacture of brake drums of cargo vehicles

Abstract: The object of research: cast iron grade DSTU EN 1561 (EN-GJL-200), used for the manufacture of brake drums for KrAZ trucks. Investigated problem: obtaining the effect of resource saving by minimizing the consumption of alloying elements, while maintaining a given level of mechanical properties of cast iron. The main scientific results: experimental and theoretical confirmation of the possibility of reducing the content of Cr introduced into the alloy to increase its strength, as part of the Cr:Ni a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The increase in the amount of perlite under the action of these factors is justified, since Cr and V are strong carbide-forming elements, and the influence of Ti and Cu is twofold. At the same time, the ratio Cr:Ni=3.25:1 somewhat falls outside the range Cr:Ni=3:1-1 recommended by practice or the range given in [15], recommended for the manufacture of the same grade of cast iron for casting automotive parts -from Cr:Ni=2.2:1-2.4:1 to Cr:Ni=1.76:1. The introduction of additional vanadium and the associated increase in the amount of perlite does not contradict the conclusions of [16], where it is shown that the introduction of vanadium leads to an increase in the hardness of HB cast iron.…”
Section: Discussionmentioning
confidence: 70%
“…The increase in the amount of perlite under the action of these factors is justified, since Cr and V are strong carbide-forming elements, and the influence of Ti and Cu is twofold. At the same time, the ratio Cr:Ni=3.25:1 somewhat falls outside the range Cr:Ni=3:1-1 recommended by practice or the range given in [15], recommended for the manufacture of the same grade of cast iron for casting automotive parts -from Cr:Ni=2.2:1-2.4:1 to Cr:Ni=1.76:1. The introduction of additional vanadium and the associated increase in the amount of perlite does not contradict the conclusions of [16], where it is shown that the introduction of vanadium leads to an increase in the hardness of HB cast iron.…”
Section: Discussionmentioning
confidence: 70%
“…The brake drum with sprue system elements is presented in Fig. 1, the form technology is given in [17]. To reduce the probability of the formation of a surface defect in the form of an open shell after removing the allowance, it is necessary to increase the size of the allowance.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…The mathematical model obtained at step 5 can be represented by a regression equation in which the output vari-Engineering able ΔQ is determined from the nomogram (Fig. 3) according to the plan of the full factorial experiment 2 2 . The plan of the experiment is based on the factors φ and Δt, varied in the ranges φ = [φ min ; φ max ] and Δt = [Δt min ; Δt max ].…”
Section: Synthesis Of Optimal Air Flow Controlmentioning
confidence: 99%
“…Therefore, despite the well-known problems generated by cupola melting, for example, environmental hazards, it is problematic to abandon this process at this stage. It is cupola melting that makes it possible to obtain cast iron in large quantities with such quality indicators that are acceptable for the manufacture of machine body parts while minimizing the cost of their manufacture [1,2].…”
Section: Introductionmentioning
confidence: 99%